Santiago's Self-Discovery in Paulo Coelho's the Alchemist - Gyawali , Netralal (JMC Research Journal, 2024)
This study analyzes the multifaceted factors influencing Santiago's self-discovery in Paulo Coelho's The Alchemist. Through a qualitative close reading method, the research explores the existentialist framework that underpins Santiago's journey. The primary objective is to elucidate the elements that catalyze his transformation, focusing on key influences such as dreams and omens, the wisdom imparted by Melchizedek, the mentorship of the Alchemist, and the profound love for Fatima. Additionally, the symbolism of the desert serves as a metaphor for existential trials, while the themes of unity with nature and communication with the Soul of the World highlight the interconnectedness of all beings. This comprehensive analysis aims to equip readers and educators with a nuanced understanding of Santiago's quest for self-discovery, ultimately revealing how these diverse factors converge to shape his spiritual awakening. Through this exploration, the study affirms the significance of personal legend and the pursuit of one's dreams as central tenets of human existence.